Nutritive value and in vitro caecal fermentation of forage meal of mulberry variety YU 62 for rabbits - Vasallo, G. E.; Savón, Lourdes; Dihigo, L. E.; Cairo, J. (Cuban Journal of Agricultural Science, 2018)
The objective of this study was to determine the nutritional value and in vitro caecal fermentation in mulberry forage meal, variety YU 62, for rabbits. A completely random design was used, analyzing six times the samples of mulberry variety YU 62 forage meal with Medicago sativa (lucerne) as control. An in vitro simulation of digestive process in anatomical segments of stomach, duodenal and caecal gastrointestinal tract of rabbit was made. In stomach phase, high calcium content in mulberry raised the pH. In the duodenal phase, a lower pH with a suitable acid-base balance was obtained, which produced an increase in digestibility of crude protein (P <0.0001) in mulberry forage meal with value of 54.92 % vs 36.4% respectively of lucerne control. In the caecal phase, in mulberry meal, digestibility of dry matter was higher than the values found in lucerne influenced by the higher digestibility for NDF. This is due to its high content of hemicellulose in the cecum and has a favorable effect on the activity of the caecal microbiota that coincides with the increase of short-chain fatty acid mainly acetic and butyric with significant difference (P <0.0001) with lucerne. In addition, it should be noted that increasing short chain fatty acids lowers pH, tending to neutrality. It is suggested that mulberry forage meal variety YU 62 has a positive in vitro nutritive value, so that it could be used instead of lucerne as an alternative raw material in the formulation of diets for rabbit feeding. Key words: rabbit, mulberry, in vitro nutritional value